Economics of Regulatory Compliance in the Fisheries of Indonesia, Malaysia and the Philippines - Achmad S. Darminto, Indah Susilowati (1998)

(untitled)
This study examines non compliance behaviour of fishers with a zoning regulation under a condition of limited enforcement in the fisheries of Indonesia, Malaysia and the Philippines. Rational utility theory is used as a framework for explaining compliance behaviour. A stratified random sample of 568 fishers from Pekalongan and Juwana in Indonesia, Kuala Kedah, Kedah in Malaysia and Conception, Ilo-ilo City, Roxas City and Tigbauan in the Philippines are used in the analysis. Fishing effort and fish landings from the various gears in the three countries were standardised using the geometric index approach. Economic models of non compliance behaviour using Logit, Probit and Tobit techniques were estimated. The results indicated that economic, morality and social influence factors determined the violation decision of individual fishers to fish in the prohibited area. Some of the legitimacy variables failed to influence the violation decision of respondents in the study. The legitimacy variables were not as important as the moral development variable in explaining the compliance behaviour. This result is consistent with the findings of Paternoster et. al. (1984) that morality has a stronger influence on law breaking behaviour and compliance rather than legitimacy. Nevertheless, the reliability test for the 12 legitimacy variables were good with overall Cronbach' s alpha of 73.7%. In general the findings of the study were consistent with the theoretical model of compliance behaviour developed in Chapter IV and the related literature reviewed in Chapter III. In practice, probability of detection were low and violation rates were high especially for Indonesia and the Philippines given their limited resources for enforcement and a large geographical area to monitor. In theory, the level of compliance can be improved by increasing the probability of detection and conviction or penalties rate. This can be done by either improving the enforcement process and! or its intensity. However, it is not very practical because of large financial requirements. To improve fishers' compliance in the study area there is a need to use other determinants of compliance such as morality and social influence factors. In Indonesia and the Philippines, enforcement institutions are not as well established as in Malaysia. Therefore, institutions of enforcement should be given priority in Indonesia and the Philippines. In Malaysia a fairly well developed enforcement institutions exist, thus in this case there is a need to enhance the scheme and implement enforcement more effectively. To improve compliance, fisheries management authorities should also explore alternative approaches for managing fisheries. One such approach is the co-management approach.